A comprehensive spectral and in silico analysis on the interactions between quercetin, isoquercitrin, rutin and HMGB1. (1st November 2022) - Shen, Pingping; Peng, Yan; Zhou, Xiaoyang; Jiang, Xuewa; Raj, Richa; Ge, Haixia; Wang, Weiwei; Yu, Boyang; Zhang, Jian
Abstract: The intake of quercetin and its glycosides has been proven to effectively reduce the level of high mobility group protein 1 (HMGB1) and the degree of inflammation, but the underlying structural mechanism is still unclear. In this study, the direct interaction between HMGB 1 and quercetin, isoquercitrin, and rutin was recorded by surface plasmon resonance (SPR). The binding interactions led to the intrinsic fluorescence quenching of HMGB1 through static quenching mechanism based on fluorescence spectroscopy. Circular dichroism (CD) spectra showed a decrease in α-helical content of HMGB1 with a slight impact on the thermal stability of HMGB1. Furthermore, molecular simulations displayed three flavonoids-HMGB1 complexes maintained primarily by hydrogen bond and hydrophobic force, confirming the strong association with Phe14. Besides, co-treatment of quercetin could significantly ameliorate HMGB1-stimulated nitric oxide release in RAW264.7 cells. These intrinsic characteristics on the interaction of quercetin, isoquercitrin, and rutin with HMGB1 protein could be conducive to understanding the molecular mechanisms of flavonoids in HMGB1-related inflammatory diseases. Highlights: Quercetin, isoquercitrin, rutin showed a direct interaction with HMGB1. Three flavonoids led to changes of HMGB1's hydrophobicity and spatial conformation. Three complexes were maintained by hydrogen bonding and hydrophobic interactions. Co-treatment with quercetin and derivatives reduced HMGB1-stimulated inflammation.